TINGKAT KEMAMPUAN MOTORIK SISWA EKSTRAKURIKULER LOMPAT JAUH SMP NEGERI 7 TAMBUSAI UTARA - Danial, Muhammad; Janiarli, Masdi; Putra, Muarif Arhas (Journal Of Sport Education and Training, 2020)
This purpose of the reseach was to determine the level of motorik skills of long jump extracurricular students in SMP Negeri 7 Tambusai North. This research is a descriptive study with a quantitative approach. The method was used survey. The population of this research was all of the Long Jump Extracurricular Students in SMP Contry 7 Tambusai North by 15 students. The instruments used were the Barrow Motor Ability Test, including Standing Broad Jump, Soft Ball Throw, Zig-Zag Run, Wall Pass, Medicine Ball Put, and 60 Yard Dash Running. The data analysis technique was used descriptive percentage analysis. The results showed that students' motorik skills were known to be in the very high category by 2 students (13%), were in the high category by 3 students (20%), were in the moderate category by 5 students (33%), were in the poor category as many as 2 students (13%), and are in the category of very less as many as 3 students (20%). So, it can be concluded that the Motorik Skills of the Long Jump Extracurricular Students in SMP Contry7 Tambusai North was in the moderate category (33%).